Exploring the divide between dental clinicians and academics for more inclusive partnerships: perspectives on building a research network - Maria Zych; Carilynne Yarascavitch; Amir Azarpazhooh; Joanna Sale (BMC Oral Health)
Abstract Introduction Dentists experience barriers of applying knowledge at point of care. In recent years, integrated knowledge translation (IKT) efforts, such as dental practice research networks, have been established in the US and other countries to overcome the potential barriers to dental clinicians being involved in research. In Canada, there is no formal network. The objective of this study was to explore the perceptions of dental clinicians and academics in building a network in Ontario that would encourage research collaboration. Methods Semi-structured interviews were conducted to collect data from dental clinicians and academics in Ontario dental schools. Purposeful sampling was used to recruit participants from the Faculty of Dentistry at the University of Toronto and Schulich School of Dentistry at Western University. Interviews were conducted via Zoom meetings between July and November 2023. Interviews were recorded, de-identified, transcribed, and analyzed using thematic analysis. Strategies to promote rigour were applied throughout the research process. Results Twenty-six interviews were conducted (twelve dental clinicians and fourteen academics). Most participants described a divide impacting many aspects of oral health research. This divide appeared to be originating from historical cultural norms rooted in the development of organized dentistry in Ontario, current financial strains faced by dentists, and misalignment of values that resulted in miscommunications between dental clinicians and academics. Despite the divide, there appeared to be a strong desire among participants to “bridge the divide”. Suggestions included starting a small network of interested individuals, enforcing existing collaborations within the universities, identifying champions in organized dentistry to advocate for establishing a formal network in Ontario, and exploring opportunities to support such a network in Canada. Discussion Despite the divide between dental clinicians and academics in oral health research, there appeared to be a strong desire to bridge the divide. This study is novel in that it reports dental clinicians’ and academics’ perceptions and experiences with IKT partnerships in dentistry. We offer recommendations for oral health professional leaders to build a new network.